Contribution of bamboo charcoal interconnection in double electrodes to evaluate the photovoltaic performance. (October 2022) - Teng, Genhui; Qin, Xiang; Gan, Yufeng; Heng, Yingqi; Hu, Dongying
Graphical abstract: Highlights: Construction of DSSCs electrodes (P25/BC photoanode and MBCF counter electrode). In DSSCs, the PCE of P25/BC-Pt (6.27%) is much higher than that of Pure P25-Pt (4.96%). MBCF shows good catalytic activity of for I3 − behaving high PCE of P25/BC-MBCF. Our work aims to provide a simple-green way to prepare bamboo charcoal-based DSSCs. Abstract: Bamboo charcoal (BC)-doped titanium dioxide (P25/BC) and modified BC (MBC) loaded with Fe3 O4 (MBCF) were used as double electrodes to improve the power conversion efficiency (PCE) of a dye-sensitized solar cell (DSCC). BC was doped into the P25 photoanode, and P25 improved dye adsorption and reduced the transfer impedance of photogenerated electrons. The PCE of P25-Pt (4.96%) was 6.27% higher than that of P25/BC-Pt. MBC contained more structural defects, and the oxygen-containing reactive groups generated on its surface combined with Fe 3+ ions, resulting in a uniform loading of Fe3 O4 on MBC. The high electrocatalytic performance of Fe3 O4 with the abundant structural defects of MBC reduced the charge transfer resistance and provided fast electron transfer paths, giving MBCF good electrical conductivity and electrocatalytic activity. DSSCs assembled using the P25/BC photoanodes and MBCF-2 CE showed a PCE of 4.27%. Electrochemical performance tests of MBCF-2 showed a specific capacitance of 150 F/g at 1 A/g and capacitance retention of 91.1% after 5000 cycles. The results demonstrate that BC has potential electrocatalytic and energy storage applications, and this paper provides a feasible strategy for applying biomass carbon-based materials in DSSCs.